2011
DOI: 10.1177/097491011100300302
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Middle Income Trap, Why do Countries Fall into It, and How Can It Be Avoided?

Abstract: The risks of falling into the Middle Income Trap have increasingly become a focus of discussions on the long-term economic and social development prospects of developing countries. These risks, and how to minimize them, are being debated at the highest levels of policy making in some of the fastest growing emerging economies, even while these countries remain a source of envy to the rest of the world. The term Middle Income Trap is by now also being widely used in economic literature as well as business-orient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
133
0
25

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(168 citation statements)
references
References 1 publication
2
133
0
25
Order By: Relevance
“…1 Several years later, Kharas and Kohli (2011) made another quite early contribution by raising the following questions:…”
Section: Introductionmentioning
confidence: 99%
“…1 Several years later, Kharas and Kohli (2011) made another quite early contribution by raising the following questions:…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al (2004) and Kohli (2011) found that this happened for the rupee in the early 2000s. The renminbi gap has narrowed since the GFC, but the rupee gap has widened instead.…”
Section: Onshore and Offshore Short-term Interest Ratesmentioning
confidence: 99%
“…The notion of the middle-income trap was proposed in a World Bank report, An East Asian Renaissance: Ideas for Economic Growth (Gill and Kharas 2008), and in Kharas and Kohli (2011). In these and other works the authors describe the middle-income trap as a situation in which 'countries that avoid the poverty trap and grow to middle-income levels subsequently stagnate and fail to grow to advanced-country levels' (Kharas and Kohli 2011, p. 281).…”
Section: What Is the Middle-income Trap?mentioning
confidence: 99%
“…South Africa, despite its membership of the G20 and the BRICS (Brazil, Russia, India, China, and South Africa) group of economies, remains mired in a cycle of low, single-digit GDP growth. This experience can be located within a broader phenomenon first described by Gill and Kharas (2008) and Kharas and Kohli (2011), as representative of a middle-income country growth trap. 3 So why, when South Africa shares so much in common with rapidly growing emerging markets, and has one of the largest and most diversified sub- Saharan African economies, has the country failed to converge …”
Section: Middle-income Country Growth Traps: the Case Of South Africamentioning
confidence: 99%